2021
DOI: 10.1155/2021/1455052
|View full text |Cite
|
Sign up to set email alerts
|

“Relief‐Retaining” Control Technology of Floor Heave in Mining Roadway with Soft Rock: A Case Study

Abstract: The floor heave problem is one of the important factors affecting the stability and safety of surrounding rocks of roadways, especially in deep high-stress mining roadway with soft rock. The return airway of no. 130203 working face in Zaoquan Coal Mine of Ningdong Mining Area in Northwest China is the research object in this study. Firstly, an innovative “relief-retaining” control scheme of floor heave is proposed, which is the comprehensive measure of “cutting groove in floor + drilling for pressure relief at… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 21 publications
0
4
0
Order By: Relevance
“…Chen et al [13] proposed an innovative "relief-retaining" control scheme of foor heave, which is the comprehensive measure of "cutting groove in foor + drilling for pressure relief at roadway side + setting retaining piles at the junction of roadway side and foor." Yang and Zhang [14] put forward the pressure-relief slot to prevent foor heave, established the mechanical model of the pressure-relief slot, and gave a method to determine the width of the pressure-relief slot.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Chen et al [13] proposed an innovative "relief-retaining" control scheme of foor heave, which is the comprehensive measure of "cutting groove in foor + drilling for pressure relief at roadway side + setting retaining piles at the junction of roadway side and foor." Yang and Zhang [14] put forward the pressure-relief slot to prevent foor heave, established the mechanical model of the pressure-relief slot, and gave a method to determine the width of the pressure-relief slot.…”
Section: Introductionmentioning
confidence: 99%
“…Most studies are based on the results of numerical simulations because there are the best ways to model the magnitudes and spatial distribution of deformations [26]. Zhao et al [8], Chen et al [13], Guo et al [21], Zhang and Shimada [22], and Zhou et al [27] used a FLAC3D simulation. Kulatilake et al used 3DEC software to simulate highstress roadways and proposed the use of 3 m bolts and inverted arch roadways to control the surrounding rock [25].…”
Section: Introductionmentioning
confidence: 99%
“…Zhai et al [6] studied the floor heave mechanism in water-rich soft rock roadways and built an asymmetric floor heave mechanical model. Chen et al [7] proposed the "pressure relief-support" control scheme to solve the floor heave problem in the Zaoquan Coal Mine. Through experiments, Sun et al [8] found that horizontal stress has a great impact on the floor heave of roadways and that rock mass failure is often accompanied by abnormal temperature changes.…”
Section: Introductionmentioning
confidence: 99%
“…By analyzing the deformation reasons of deep high-stress soft rock roadway, Yang et al [11] proposed a combined supporting technology to coordinate nonuniform deformation of surrounding rock, control squeeze ow of oor heave, and strengthen the bearing structure of the surrounding rock. Chen et al [12] put forward an innovative "relief-retaining" control technology of oor heave, which is a comprehensive measure that is composed of cutting groove in the oor, drilling for pressure relief at the roadway side, and setting retaining piles at the junction of roadway side and floor. Based on numerical simulation, Zheng et al [13] improved the bearing structure of support and proposed a high-strength combined support system with higher integrity and bearing capacity, which is consisted of cable bolt, fiber-reinforced shotcrete, steel mesh, split sets, resin bolt, and cement grouting.…”
Section: Introductionmentioning
confidence: 99%